2010
DOI: 10.2478/s11658-010-0020-6
|View full text |Cite
|
Sign up to set email alerts
|

Gender dimorphism in the exercise-naïve murine skeletal muscle proteome

Abstract: Skeletal muscle is a plastic tissue with known gender dimorphism, especially at the metabolic level. A proteomic comparison of male and female murine biceps brachii was undertaken, resolving an average of 600 protein spots of MW 15-150 kDa and pI 5-8. Twenty-six unique full-length proteins spanning 11 KOG groups demonstrated statistically significant (p<0.05) abundance differences between genders; the majority of these proteins have metabolic functions. Identified glycolytic enzymes demonstrated decreased abun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 16 publications
2
11
0
Order By: Relevance
“…In this regard, we hypothesized that male rats undergo slower fat oxidation, thereby leading to excessive accumulation of dietary fat in white adipose tissues when compared with female rats. Similar genderdimorphism was observed in non-exercised mice muscle [73].…”
Section: Proteins Showing Gender Differences Only In Hfd Rats (Group Iv)supporting
confidence: 65%
“…In this regard, we hypothesized that male rats undergo slower fat oxidation, thereby leading to excessive accumulation of dietary fat in white adipose tissues when compared with female rats. Similar genderdimorphism was observed in non-exercised mice muscle [73].…”
Section: Proteins Showing Gender Differences Only In Hfd Rats (Group Iv)supporting
confidence: 65%
“…Therefore, down-regulated troponin T fast may result in loss of muscle force and contractile speed when exposed to HFD. This pattern was confirmed by the significantly decreased Troponin T fast at both the protein level [26] and transcript level [24] in the muscle of other determinants of force and velocity in muscle fibers [31]. It is interesting to note that myosin light chain 1 (MLC1) was dominantly expressed in gastrocnemius muscle and showed weak gender differences, whereas MLC3 was dominantly expressed in soleus muscle with significant gender dimorphism.…”
Section: Proteins Involved In Muscle Contractionmentioning
confidence: 49%
“…Metskas et al [26] analyzed the skeletal muscle proteome and found that glycolytic enzymes were less abundant in females, which suggests that females rely on lipid oxidation more than males. However, two glycolytic proteins (GP and -enolase) identified in this study did not show gender differences and differences were only observed in response to the HFD.…”
Section: Metabolic Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, several proteomics studies have been conducted in an effort to reveal gender differences in protein expression patterns in blood [37,38], muscle [39], kidney [40], brain [41], and sperm [42]. However, to the best of our knowledge, no comparative proteomic study in biofluids or metabolic organ tissues of lean and obese animal models for examination of protein abundance and/ or regulation patterns between genders has been conducted.…”
Section: Introductionmentioning
confidence: 99%